Modeling delamination of fire insulation from steel structures subjected to blast loading. (1st June 2016) - Arablouei, Amir; Kodur, Venkatesh
Highlights: Delamination of fire insulation from a steel column is modeled under blast loading. Delamination of three types of fire insulation from steel structures is studied. Cohesive zone modeling with contact interaction analysis is simulated. A parameter for delamination of fire insulation under blast loading is proposed. Abstract: This article presents a fracture mechanics-based numerical approach for quantifying delamination of spray-applied fire-resistive material (SFRM) from a steel beam–column subjected to a blast loading. In the numerical model, cohesive zone model is employed to simulate interfacial crack initiation and propagating at the interface of SFRM and steel. Three types of SFRM, widely utilized in the practice namely, mineral fiber-based, gypsum-based and Portland cement-based SFRM are considered in the analysis. The numerical model is validated against two sets of experiments; a full scale blast test on a steel beam–column and a drop mass impact test on a steel beam insulated with SFRM. The verified numerical model is subsequently utilized to carry out extensive parametric study to quantify critical factors that can influence the extent of delamination of SFRM from a steel beam–column, namely fracture energy at steel-SFRM interface, elastic modulus of SFRM, thickness of SFRM, and the level of blast overpressure. Results from parametric studies show that Portland cement-based SFRM can provide the highest level of resiliency in terms of withstanding the applied blast overpressure, while mineral fiber-based SFRM shows the lowest level of endurance. Further, the outcomes obtained from parametric study demonstrate that the extent of delamination can directly be related to blast overpressure and thickness of SFRM, whereas it can inversely be related to elastic modulus and fracture energy of SFRM. Based on the results of parametric study, a delamination characteristic parameter, which incorporates the major factors influencing the delamination, is defined and the extent of delamination is expressed as a function of this parameter.